Implantação de bundle de prevenção de lesão por pressão em unidade de terapia intensiva - Santos, Ramon Araújo dos (2023)
Pressure injuries pose significant challenges for healthcare institutions and intensive care units, primarily due to their status as predictable adverse events. Despite the increasing amount of evidence on preventive measures for pressure injuries in recent years, there are several obstacles to implementing and translating these practices into the daily routines of healthcare teams. In light of this, care bundles or packages have emerged as a collection of evidence-based preparatory practices collectively developed to enhance the quality of care. General objective: To implement best practices aimed at improving the quality of care for patients in the intensive care unit (ICU), specifically focusing on the prevention of pressure injuries. Specific objectives: Conduct a situational diagnosis of the ICU concerning the best practice recommendations for pressure injury prevention in adult patients; Identify the barriers and enablers that affect compliance with these recommendations; Develop and implement a pressure injury prevention bundle designed for adult ICU patients; Monitor and assess changes in compliance with the recommended practices following the implementation of the pressure injury prevention bundle. Method: The research employed a participatory approach based on the theoretical framework of implementation science. It was conducted in an Adult Intensive Care Unit (ICU) of a teaching hospital in the State of Espírito Santo, Brazil. The multidisciplinary team, consisting of nurses, nursing technicians, physiotherapists, nutritionists, and social workers, actively participated in the research. A multidisciplinary working group within the institution was formed to collaborate on developing strategies to reduce pressure injuries. The study was divided into 5 steps, and the Plan-Do-Check-Act (PDCA) cycle was utilized. In the 1st step, a situational diagnosis was carried out using mixed methods to assess the existing conditions and practices related to pressure injury prevention. The 2nd step involved the elaboration of a pilot bundle, which consisted of a set of evidence-based practices aimed at preventing pressure injuries. In the 3rd step, the bundle's content, face, and validation were evaluated to ensure its appropriateness and effectiveness. The 4th step focused on the implementation of the bundle through theoretical and practical training for the healthcare team. Adherence to the bundle recommendations was monitored for one month. The 5th step involved an evaluation of the implementation process, where barriers and facilitators were identified using the Consolidated Framework for Implementation Research (CFIR), a qualitative approach. Qualitative data analysis utilized thematic analysis, while quantitative data underwent descriptive analysis. Results: The first intensive care unit pressure injury prevention bundle was collectively built. The acronym ACERT was created to name the bundle, based on five main categories: A: Skin assessment and pressure injury risk; C: Skin care and moisture management; E: Patient and caregiver involvement; R: Repositioning and support surface; T: Nutritional therapy. After the trainings, the material was evaluated by the care team as adapted to meet the local reality, with quality interventions, low cost, and low complexity. The main facilitators for implementation were the realization of trainings and availability of materials for prevention, and the main barrier was the lack of engagement and commitment from the team. Monitoring presented satisfactory adherence results, except for categories and recommendations that require material acquisition and work process adjustments. Products: Pressure injury prevention bundle, educational graphic material to install on monitors, data collection tool. Conclusion: Implementing a pressure injury prevention bundle has a high impact on the quality of care. The research products are already incorporated into daily work in the unit, generating positive results since their implementation. The importance of collectively building protocols generates better acceptance and ownership of the practice by the team. Thus, monitoring adherence indicators and in-service training favor the maintenance of good practices. This research presents in a systematic way, based on the theoretical framework of implementation science, the step-by-step of implementing good practices, with the potential for expansion to other internal hospital sectors and even other realities at the national level.